Outlook on nutritional importance and breeding strategies for oil and quality improvement in sesame (Sesamum indicum L.) - Ganesh Babu, S R V N; Saraswathi, R; Mahalingam, A; Paramasivan, M; Manivannan, N (Plant Science Today, 2024)
Sesame (Sesamum indicum L.), is a pivotal crop in global agriculture due to its high oil content (50-60 %), rich in quality unsaturated fatty acids and an array of bioactive compounds like sesamin and sesamol. This review is a compilation of information on sesame nutrition, mechanism of action of bioactive principles, health benefits in terms of unsaturated fats, antioxidants and essential nutrients to combat health disorders. The genetic resources are the base for any crop improvement programs. The genetic wealth of this crop as ex-situ conservation world-wide, traits of importance from its wild relatives, studies on genetic diversity through agronomic and molecular techniques for quality traits are focused. Both conventional and molecular breeding methods are examined. Conventional breeding efforts covers trait variability, correlations, gene action, combining ability studies, breeding methods and varieties released. The insights into molecular biology probes the novel QTLs, discovery of candidate genes, molecular markers for quality traits, genome sequencing, advancements in gene expression studies, genetic maps and pangemone. Despite the significant progress, the lacuna and future prospects in these areas are highlighted. Integrating the information from modern genomic technologies with conventional methods is the key to maximize the crop's potential for oil and nutritional security.